They Spear, Hit Again, Bite, Get Engaged and Sometimes Marry: Revisiting the Gendering of Kula Shells - Kuehling, Susanne (Anthropologica, 2012)
This article revisits the ethnography of kula exchange and proposes a fresh perspective on gender as a strategy of kula talk. The shell ornaments that are used in kula have often been classified as "male" and "female." Here, I argue that these are not inherent qualities of kula valuables but flexible tropes of kula talk. The wider context of kula exchange rhetoric and gen der demonstrates that male and female invoke the imagination of sexual relations, of pleasure, intimacy and consent. Gender symbolism, in kula, is a rhetorical strategy to lubricate the sense of trust between kula exchange partners.